2015
DOI: 10.1021/acs.jpcc.5b04930
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Greater-Than-Bulk Melting Behavior of Ga–Al Nanoalloys

Abstract: Phase diagrams are the most reliable way of predicting phase changes in a system. In this work, we create the phase diagram of the Ga (20-x) Al x + bimetallic cluster system, for which the monometallic clusters display greater-thanbulk melting behaviour. Employing first-principles Born-Oppenheimer molecular dynamics in the microcanonical ensemble, we describe the solid-liquid-like phase transition in two distinct compositions Ga 11 Al 9 + and Ga 3 Al 17 + . The clusters show peaks in specific heat at 824 K and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Ojha et al reported that for Ga (20Àx) Al x + , the specific heat peaks exceed the bulk melting temperatures. 29 The limited availability of experimental and theoretical calculations on boron-aluminum, aluminum-gallium, and gallium-boron nanoalloys compared to their unary clusters prompted us to conduct a systematic investigation of unary, binary, and ternary clusters comprising boron, aluminum, and gallium. In this study, the analyzed binary clusters are denoted as B l Al m , Al l Ga m , and B l Ga m (1 r l and m r 6; l + m r 12), whereas the ternary clusters are denoted as B l Al m Ga n (l, m, n = 1-4; l + m + n r 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ojha et al reported that for Ga (20Àx) Al x + , the specific heat peaks exceed the bulk melting temperatures. 29 The limited availability of experimental and theoretical calculations on boron-aluminum, aluminum-gallium, and gallium-boron nanoalloys compared to their unary clusters prompted us to conduct a systematic investigation of unary, binary, and ternary clusters comprising boron, aluminum, and gallium. In this study, the analyzed binary clusters are denoted as B l Al m , Al l Ga m , and B l Ga m (1 r l and m r 6; l + m r 12), whereas the ternary clusters are denoted as B l Al m Ga n (l, m, n = 1-4; l + m + n r 12).…”
Section: Introductionmentioning
confidence: 99%
“…Ojha et al reported that for Ga (20− x ) Al x + , the specific heat peaks exceed the bulk melting temperatures. 29…”
Section: Introductionmentioning
confidence: 99%
“…Based on this surprising revelation, a flurry of computational simulations based on Born–Oppenheimer molecular dynamics followed in attempting to identify the origin of this unanticipated finite-temperature behavior. Simulations that followed over the years attempted to discern the conformational dynamics followed by the various-sized clusters and the origin of their enhanced thermal stabilities. These computational studies also further revealed that the shape- and size-specific clusters of Au and Sn have enhanced thermal stability as compared to their bulk counterparts, thereby indicating it to be a more general property than thought of among the atomic clusters. , Along with these newer aspects, detailed simulations also highlighted interesting aspects such as the fluxionality of clusters and/or role of factors such as charge in enhancing the stability of a given conformation at finite temperatures. Several studies continue to follow where the thermal stability of a given conformation or alloy is explored using first-principles-based molecular dynamics. …”
Section: Introductionmentioning
confidence: 99%